Flow rate and flow equation of pharmaceutical free-flowable powder excipients - Sklubalová, Zdenka; Zatloukal, Zdenek (Pharmaceutical development and technology, 2013)
Basic aspect of powder handling is powder flow which depends on mechanical properties of the solid material. This experimental work presents the results of flowability testing of the free-flowable particle size fraction of 0.0250-0.0315 cm of five powder excipients. The single-point determination of the mass flow rate from a cylindrical, flat-bottomed hopper was primarily influenced by the diameter of a circular orifice. The significant effect of the orifice height was also noted. Increasing the orifice height, the flow under gravity is directed resulting in the sudden acceleration of the flow rate. The critical zone relates to the orifice diameter. The multi-point determination of flowability employed the actual parameters of the flow equation which allows the prediction of the mass flow rate. The precision of the prediction was the basic criterion in optimization of the orifice geometry. Based on the results, the orifice height of 1.6 cm can be recommended for the correction of faster powder flow. For the slower powder flow, an orifice height of 0.2 cm can be used alternatively. In conclusion, the information about the orifice height used should be referred to whenever test the powder flowability and compare the results.
Keywords: farmaceutická chemie; velikost částic; pomocné látky; prášky, zásypy, pudry; Excipients; příprava léků; Drug Compounding; Chemistry, Pharmaceutical; Particle Size; Powders